2017
DOI: 10.1093/nar/gkx509
|View full text |Cite
|
Sign up to set email alerts
|

Tethering not required: the glucocorticoid receptor binds directly to activator protein-1 recognition motifs to repress inflammatory genes

Abstract: The glucocorticoid receptor (GR) is a ligand-regulated transcription factor that controls the expression of extensive gene networks, driving both up- and down-regulation. GR utilizes multiple DNA-binding-dependent and -independent mechanisms to achieve context-specific transcriptional outcomes. The DNA-binding-independent mechanism involves tethering of GR to the pro-inflammatory transcription factor activator protein-1 (AP-1) through protein-protein interactions. This mechanism has served as the predominant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 69 publications
3
52
0
Order By: Relevance
“…38). In support of our view, other studies have demonstrated that activated GR preferentially suppresses the function of AP-1 family members (39,40). In addition, synergistic upregulation of SGK1 expression by E 2 and dexamethasone facilitates maintenance of the homeostasis in the endoplasmic reticulum to antiapoptosis (41,42).…”
Section: Discussionsupporting
confidence: 86%
“…38). In support of our view, other studies have demonstrated that activated GR preferentially suppresses the function of AP-1 family members (39,40). In addition, synergistic upregulation of SGK1 expression by E 2 and dexamethasone facilitates maintenance of the homeostasis in the endoplasmic reticulum to antiapoptosis (41,42).…”
Section: Discussionsupporting
confidence: 86%
“…Given the strong repressive activity of the GRtetra receptor, we propose that transrepression as previously defined cannot entirely explain GR repressive action. In fact, both JUN-FOS and NFKB1 pathways are most likely modulated by GR in a more complex manner that involves, at least in part, an oligomeric receptor interacting directly with the chromatin landscape (Weikum et al 2017;Hudson et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the analysis of GR occupancy nearby our candidate Dex-sensitive genes of both classes reveals co-localized GR and p65 peaks associated with NF-kB enhancers under repressing LPS + Dex conditions and no GR binding in Dex-only - treated macrophages. Thus, although this is certainly not the only mechanism by which GR affects inflammatory gene expression ( Rao et al, 2011 ; Uhlenhaut et al, 2013 ; Oh et al, 2017 ; Weikum et al, 2017a ), tethering to p65 is a widespread regulatory mechanism that GR relies upon to elicit acute repression of pro-inflammatory genes in macrophages.…”
Section: Discussionmentioning
confidence: 99%